The Role of Environmental Education and Green Supply Chain Practices in Achieving Sustainable Development: Evidence from Indonesia - Parmawati, Rita; Mulyadi, Fadli; Rosyani, Rosyani; Suaedi, Suaedi; Yunikewaty, Yunikewaty (International Journal of Energy Economics and Policy, 2023)
Globally, environmental education and green supply chain (GSC) practices are considered essential elements for sustainable development, and this aspect needs new literature and policymakers' attention. Hence, the present article examines the impact of GSC practices on the sustainable development of manufacturing organizations in Indonesia. The article also investigates the moderating role of environmental education among green purchasing, IEM, and sustainable development in manufacturing organizations in Indonesia. The study applies primary data collection technologies such as survey questionnaires to gather primary data from respondents. The study also applies the smart-PLS to test the association among variables. The outcomes revealed that eco-design, green purchasing, and IEM have a positive linkage with sustainable development in manufacturing organizations in Indonesia. The outcomes also exposed the environmental education significantly moderating among green purchasing, IEM, and sustainable development in ABC organizations in Indonesia. The article guides the regulators in developing regulations regarding sustainable development using GSC practices and environmental education.